2009
DOI: 10.1007/s10563-009-9076-6
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metal Sintering Suppression Technology in Three-way Catalyst: Automotive Three-way Catalysts with the Noble Metal Sintering Suppression Technology Based on the Support Anchoring Effect

Abstract: This paper reviews the progress in our development of the three-way catalyst with a noble metal sintering suppression technology based on the support anchoring effect. The catalytic activity on this catalyst is far superior to the conventional catalyst, but with lower noble metal loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 23 publications
1
36
0
1
Order By: Relevance
“…In TWCs, H2O acts as an oxidizing agent for CO conversion by the water-gas-shift reaction and for steam reforming of hydrocarbons [4]. H2O also significantly affects the thermal stability of the metals (Pt, Rh and Pd) present in the TWC as well as the support, mostly through sintering mechanisms [4,27,28] and by changes in the Pd oxidation state during hydrothermal aging [29]. Water may also act as a reaction inhibitor by adsorption onto the catalyst.…”
Section: Effects Of H 2 O On Ch 4 Oxidation Over Pd Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…In TWCs, H2O acts as an oxidizing agent for CO conversion by the water-gas-shift reaction and for steam reforming of hydrocarbons [4]. H2O also significantly affects the thermal stability of the metals (Pt, Rh and Pd) present in the TWC as well as the support, mostly through sintering mechanisms [4,27,28] and by changes in the Pd oxidation state during hydrothermal aging [29]. Water may also act as a reaction inhibitor by adsorption onto the catalyst.…”
Section: Effects Of H 2 O On Ch 4 Oxidation Over Pd Catalystsmentioning
confidence: 99%
“…Lamber et al [46] suggested that on SiO2 in the presence of H2O, the formation of silanol (Si-OH) groups favors the migration and coalescence of Pd, whereas in the absence of H2O, Ostwald ripening is favored. Sintering suppression has been demonstrated for Pt catalysts using supports that enhance metal-support interactions [28]. Nagai et al [47] demonstrated a correlation between the O electron density of the support, the strength of the Pt-O interaction and the resulting crystallite size.…”
Section: Catalyst Sintering By H2omentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the total demand of PGMs for automotive catalysts is growing due to increasing environmental awareness [6]. Studies of ways to reduce the use of PGMs or to develop alternative technologies are gaining extensive attention as a result [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Forexample,supported Au catalysts were suggested to be promising for automotive pollution control [5] in which there is an eed to convert CO at low temperatures. [9] Thelower stability of Au catalysts is mainly because of the low Tammann temperature of Au (395 8 8C). [7] However, the catalysts used in modern cars have to stand temperatures in excess of 800 8 8C, which can cause severe sintering of Au NPs.…”
mentioning
confidence: 99%